2021
DOI: 10.1097/md.0000000000026361
|View full text |Cite
|
Sign up to set email alerts
|

Improving work-life balance among administrative officers in Catholic primary schools

Abstract: Objective: Work-life balance (WLB) is an essential precursor of workers’ mental health. The theory of rational emotive behaviour therapy proposes that an imbalance in work and family life may result from people's dysfunctional perceptions of their work and other aspects of their personal life. Also, the constructive philosophies of rational emotive behavior therapy are said to be congruent with most religious belief systems of Christian clients. Therefore, our research examined the efficacy of Chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…These findings are similar to previous RREBT depression treatment research [27] which also reported significant Time effect as well as significant Time and Group interactions. Our findings also support those of Iremeka et al [22] and Uzodinma et al [24] whose RREBT-based studies demonstrated significant interactions of Time and Group on the outcome measures. The implication is that compliance to the RREBT treatment plans and timing is very crucial in achieving positive outcome or desired results, that is, significant decrease in symptoms.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings are similar to previous RREBT depression treatment research [27] which also reported significant Time effect as well as significant Time and Group interactions. Our findings also support those of Iremeka et al [22] and Uzodinma et al [24] whose RREBT-based studies demonstrated significant interactions of Time and Group on the outcome measures. The implication is that compliance to the RREBT treatment plans and timing is very crucial in achieving positive outcome or desired results, that is, significant decrease in symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…[20,21] According to the RREBT model of treatment, a patient’s dogmatic religious beliefs can be examined by therapists in order to promote a mentally healthier self. [21,22] Common components of RREBT model involves the inclusion of scriptural contents and religious resources relevant to a patient’s religious traditions and religious orientations into the therapeutic process with the aim of improving their cognitive, emotional and behavioral symptoms. [22,23] Studies on the RREBT treatment approach, particularly, the Christian-oriented REBT model, showed that it had significant positive effects on the improvement of participants’ work-life balance, [22] family life, [24] and diminution of depression, automatic negative thoughts, irrational thoughts, [25] and patients’ general pathology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Employees’ career beliefs can be rational in which case, it leads to flexible, logical, appropriate, and adaptive emotions (e.g., feelings of sadness or regret for not reaching the desired goals) toward the progress of the organization. [52,53] It can as well be irrational in which case, such belief is not anchored on empirical reality and is always related to rigid, illogical, and non-extreme views (e.g., feelings of depression, anger, or humiliation of not reaching goals) which are bound to hinder the attainment of organizational objectives. [54,55]…”
Section: Introductionmentioning
confidence: 99%
“…Employees' career beliefs can be rational in which case, it leads to flexible, logical, appropriate, and adaptive emotions (e.g., feelings of sadness or regret for not reaching the desired goals) toward the progress of the organization. [52,53] It can as well be irrational in which case, such belief is not anchored on empirical reality and is always related to rigid, illogical, and non-extreme views (e.g., feelings of depression, anger, or humiliation of not reaching goals) which are bound to hinder the attainment of organizational objectives. [54,55] An irrational belief is seen in employees when they hold views that are basically controlled by their personal tendency and interest toward self, others, or situations in life (e.g., my colleagues "should, ought, or must always respect me"), hence, may always deviate from organizational norms or policies that do not support their beliefs.…”
Section: Introductionmentioning
confidence: 99%